A computational framework for finite element modeling of traveling loads on bridges in dynamic regime. (27th July 2021) - De Risi, Raffaele
Abstract: The rigorous modeling of traveling loads on bridges in a dynamic regime is not an easy task as the traveling load contributes to the dynamic of the structural system with its mass and damping. In this paper, a simplified approach for traveling loads on bridges in dynamic regime is proposed. The main simplification consists in neglecting the traveling mass. The validity of the proposed simplification is checked with a sensitivity analysis considering a few realistic case‐study bridges. The ranges of velocity and traveling‐force/bridge‐weight ratio are identified. Eventually, the proposed methodology is applied to two case studies, (i) an existing Italian reinforced concrete viaduct and (ii) a pedestrian bridge. The applications show that the proposed simplified approach can be applied to a range of civil engineering problems such as the quantification of the structural reliability of existing structures or the assessment of pedestrian comfort.